Lone-Wolf Terorisme di Indonesia: Fenomena dan Pengaturan - Sirait, G Febiola; Rapik, Mohamad; Lasmadi, Sahuri (Faculty of Law, Universitas Jambi, 2025)
Terrorism, as a form of radicalism, is an extraordinary crime that violates human rights and is condemned globally. One of its forms is self-terrorism or lone-wolf terrorism, a terror act committed by an individual. This article aims to elaborate on the phenomenon and regulation of lone-wolf terrorism in Indonesia. This article is based on normative legal research and employs legislative, conceptual, and comparative approaches to strengthen the analysis. It is concluded that lone-wolf terrorism is a troubling phenomenon for the world. However, despite the intention to limit and combat this act, there are no specific regulations addressing this issue, which allows the act to continue to spread widely Abstrak Terorisme sebagai bentuk radikalisme merupakan kejahatan luar biasa yang melanggar hak asasi manusia dan dikecam secara global. Salah satu bentuknya adalah lone-wolf terrorism, yaitu aksi teror yang dilakukan secara individu dengan memiliki motif tertentu tanpa keterkaitan dengan organisasi atau kelompok. Penelitian ini bertujuan agar memahami tentang fenomena dan pengaturan lone-wolf terrorism di Indonesia. Penelitian ini menggunakan metode hukum yuridis normatif dengan pendekatan perundang-undangan, konseptual dan kasus.